PARENTING PARENTING STYLE ORANG TUA TERHADAP KEMATANGAN EMOSI PADA REMAJA AKHIR - Mariska Della Viona; Arthur Huwae (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2026)
Adolescence is a developmental stage characterized by significant changes in various aspects of life, including emotional maturity. Many late adolescents experience emotional imbalance and conflicts related to their identity and self-roles, which can lead to stress. The purpose of this study is to determine the relationship between parents’ parenting styles and emotional maturity in late adolescents. This study employs a quantitative approach using bivariate correlation analysis. The research involved 33 late adolescent participants aged 18–21 years, selected through purposive sampling techniques. Data were collected using a Likert-scale questionnaire, specifically the Parental Authority Questionnaire (PAQ). The results showed a significant positive relationship between the father’s permissive parenting style and emotional maturity, as well as a significant positive relationship between the mother’s parenting styles (authoritative, authoritarian, and permissive) and emotional maturity. These findings can guide parents in adopting appropriate parenting styles to promote optimal emotional development in their children.